2020
DOI: 10.29333/ejgm/7874
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Genistein on the Morphine-Induced Kidney Disorders in Male Mice

Abstract: Background: Morphine is a member of the naturally occurring phenanthrene alkaloids of opium. Genistein is a phytoestrogen, present in soy products. This study was designed to evaluate protective effects of genistein against morphine induced damages to the kidneys of mice.Methods: In this study, 48 male mice were randomly assigned to 8 groups: control (saline), morphine treated group (10 mg/kg/day); genistein groups (1, 2, 4 mg/kg/day) and morphine plus genistein treated group. Drugs were administrated intraper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The previous studies also indicated that opium consumption significantly increased the WBC, platelet and neutrophil count [ 36 37 ]. Administration of morphine in an experimental study also significantly increased BUN, creatinine and nitric oxide levels compared to the control mice [ 38 ]. It has been reported that Rhabdomyolysis (proteins and electrolytes release from muscle tissue) and muscle necrosis were induced by lead poisoning [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies also indicated that opium consumption significantly increased the WBC, platelet and neutrophil count [ 36 37 ]. Administration of morphine in an experimental study also significantly increased BUN, creatinine and nitric oxide levels compared to the control mice [ 38 ]. It has been reported that Rhabdomyolysis (proteins and electrolytes release from muscle tissue) and muscle necrosis were induced by lead poisoning [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The isoflavone inhibited NF-κB, iNOS, and COX-2 activation alongside cytokines such as TNF-α, IL-6, and IL-1β [397]. Genistein improves kidney damage induced by morphine [398]. Empirical report have suggested a similar antioxidant potency for genistein and daidzein toward DNA oxidative insult [399].…”
Section: Coumarinsmentioning
confidence: 97%
“…Lactate dehydrogenase B (LDHB) more readily oxidizes lactate to pyruvate while the A subunit is involved with the reverse reaction as part of anerobic glycolysis. Both acute and chronic morphine administration (10–100 mg/kg) alter the expression level of components of the LDH complex, increasing LDHA but decreasing LDHB mRNA and protein expression; a change not observed with tramadol treatment [ 18 , 87 , 88 , 89 , 110 ]. The changes to LDH are thought to be a compensatory mechanism to help fulfil immediate energy demands.…”
Section: Glycolysismentioning
confidence: 99%
“…“+” indicates an increase in either activity, expression, or level, while “-” indicates a decrease in the aforementioned parameters. HK—hexokinase; GK—glucokinase; PGI—phosphoglucose isomerase; PFK—phosphofructokinase; ALDO—aldolase; DHAP—dihydroxyacetone phosphate; TPI—triosephosphate isomerase; GAPDH—glyceraldehyde-3-phosphate dehydrogenase; PGK—phosphoglycerate kinase; PGM—phosphoglycerate mutase; ENO—enolase; PK—pyruvate kinase; LDH-A—lactate dehydrogenase A; PD—pyruvate dehydrogenase; PC—pyruvate carboxylase; CS—citrate synthase; AH—aconitase or aconitate hydratase; IDH—isocitrate dehydrogenase; a-KGD—α-ketoglutarate dehydrogenase; SCoAS—succinyl CoA synthetase; SD—succinate dehydrogenase; FH—fumarase or fumarate hydratase; MD—malate dehydrogenase; GLS—glutaminase; GS—glutamine synthase; GDH—glutamate dehydrogenase (also known as glutamic acid decarboxylase); OXPHOS—oxidative phosphorylation; PPP—pentose phosphate pathway [ 18 , 79 , 80 , 81 , 82 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 91 , 92 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ].…”
Section: Figurementioning
confidence: 99%